Legal Analysis of the Legal Consequences of the Cancellation of the Deed of Land Sale and Purchase Agreement (Case Study of Case Number 154/Pdt.G/2022/PN.Smg) - Syahputra, Muhammad Rizqi; Suwondo, Denny (TABELLIUS: Journal of Law, 2025)
Land sale and purchase is a reciprocal agreement involving the seller and the buyer. The content of the promise in question is where one party carries out its obligations, while the other party acknowledges it or promises to provide compensation if there is a violation of the contents of the contract. The agreement is intended as a preliminary agreement of the main intention of the parties to transfer land rights. The research approach method is a normative legal approach. A research method that obtains legal knowledge by emphasizing the provisions of applicable regulatory laws. This type of research is by examining library materials and secondary data including primary legal materials, secondary legal materials and tertiary legal materials, in the form of documents or applicable laws and regulations related to this approach method. Legal protection for the fulfillment of the rights of the parties if one party defaults in the sale and purchase agreement is highly dependent on the strength and binding sale and purchase agreement made. The law on Cancellation of the Sale and Purchase Agreement is that the parties may be subject to a fine of an amount that has been agreed upon from the amount that the buyer must pay to the seller or buyer, for each day of delay. Legal Considerations from the Judge on the Cancellation of the Deed of Sale and Purchase of Land Case Number 154/Pdt.G/2022/PN.Smg, According to the author, it is in accordance with the applicable legal regulations as explained by the author previously, where in this case the Agreement ends and as far as necessary both parties release themselves from what is stipulated in Article 1266 and Article 1267 of the Civil Code, and the Seller is obliged to return the money that has been paid by the Buyer after deducting a few percent from the selling price of the land and building as a replacement for the costs incurred by the Seller plus a fine that must be paid by the Buyer to the Seller.